If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4h + -2 = 2h + 18 Reorder the terms: -2 + 4h = 2h + 18 Reorder the terms: -2 + 4h = 18 + 2h Solving -2 + 4h = 18 + 2h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-2h' to each side of the equation. -2 + 4h + -2h = 18 + 2h + -2h Combine like terms: 4h + -2h = 2h -2 + 2h = 18 + 2h + -2h Combine like terms: 2h + -2h = 0 -2 + 2h = 18 + 0 -2 + 2h = 18 Add '2' to each side of the equation. -2 + 2 + 2h = 18 + 2 Combine like terms: -2 + 2 = 0 0 + 2h = 18 + 2 2h = 18 + 2 Combine like terms: 18 + 2 = 20 2h = 20 Divide each side by '2'. h = 10 Simplifying h = 10
| 9t+5=7-2t | | 8x+13=27 | | 70=9x-2 | | 8x+3=4x-1 | | -7x+4y=-5 | | 2x-5y=-14 | | 1.10=1.00+x+x | | 11x+2y=-8 | | 49y^2-25=1 | | 35=5+2c | | x=843-53 | | -6(2x-1)-(3x+5)=32 | | x*x-3x-28=0 | | 8y+3=7y-1 | | Y=x^2-8 | | 5x+8=3x+32 | | X+5+x=25 | | 6x+13+4x=10(x+3) | | 4(x+1)+5(3x-3)=-30 | | -x/6-2=1 | | -x/6-2=2 | | -x/6-2=3 | | -6(t-2)-(t+7)=7 | | 10x=4x^2-6 | | 5k+13=3 | | 40-8+5= | | 5z-1=9z+1 | | 5z-1=15z-3 | | 168x-48=120x-96 | | 2t-4=3(t+5) | | c=3+1.5h | | 2x^2-11x=0 |